THE RELATIONSHIP BETWEEN LEARNING DISCIPLINE, PEER INTERACTION, AND STUDENT PERCEPTION OF TEACHER MATHEMATICS SUBJECTS WITH LEARNING RESULTS OF MATHEMATICS GRADE VII SMP NEGERI 1 PLAYEN - Intan Wahyuni; Nur Arina Hidayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
Several factors can lead to a less optimal learning process: discipline learning, peer interaction, and students' perception of a math teacher. The purpose of this study is to determine whether there is a positive and significant relationship between learning discipline, peer interaction, and students' perceptions of mathematics teachers with the results of learning mathematics students grade VII SMP Negeri 1 Playen Gunungkidul Academic Year 2016/2017. This study population is all students of class VII second Semester SMP Negeri 1 Playen Gunungkidul Academic Year 2016/2017, as amounted to 192 students in 6 classes. The sample was taken by a random sampling technique and obtained class VII A consisting of 32 students. Data retrieval technique obtained by questionnaire to know students' discipline, peer interaction, and perception of the student to teacher of mathematics and test method to know the result of student learning. The instrument test used validity tests, tests of different power, and reliability tests. Test prerequisite analyses were a test of normality, independent test, and linearity test. Data analysis for hypothesis test used correlation analysis and linear regression analysis. The results showed that there was a positive and significant correlation between learning discipline, peer interaction and student perception of mathematics teacher with mathematics learning result, obtained F count = 8,564853231 and F table (3,29) = 2,9467 with correlation coefficient double equal to 0,691760002 and double linear regression equation is three variables that is Å¶ = -80,10301 + 0,0469447 X1 + 0,4650801X2 + 1,2582694X3 big relative donation (X1) = 2,136238336%, (X2) = 14 , 28507186, (X3) = 83,5786898 and effective contribution (X1) = 1,02226%, (X2) = 6,83586, (X3) = 39,9951.